Snaking Chatter: Characteristics and Mitigation - Rimac, Luke (My University, 2025)
The work done in this thesis delves into the seldom discussed phenomenon of snaking chatter in the grooving process. Snaking chatter differs from the typical diametrical chatter in grooving as it arises from tool vibration in the lateral or axial direction of the workpiece, causing a characteristic sinuous groove profile. This causes an inconsistent increase in groove width over its nominal value, often exceeding tolerance limits in precision engineering applications. Contrary to the suggestion put forth in the current literature which attributes snaking chatter to mode coupling, this thesis proposes the alternative hypothesis that it is the result of regenerative action upon the side walls of the groove. This is conclusively proven by a series of experiments as well as examination of the chatter marks left on the side walls of the machined groove. Diametrical chatter and snaking chatter are shown to be mutually exclusive, and the use of a tuned-mass damper equipped tool, designed to eliminate diametrical chatter, enables snaking chatter to occur instead. Conventional stability lobe theory was adapted for use in snaking chatter, which showed that the infeed required to mitigate snaking chatter was too low and in the ploughing regime, and therefore not a practical solution. Due to this, a counter-intuitive mitigation strategy was developed which not only eliminates the issue of snaking chatter in grooving but also increases material removal rate by 450%.
Keywords: chatter; grooving; mode coupling; regeneration